Cloud and fog computing in 5G mobile networks - Mastorakis, George, 1978-; Mavromoustakis, Constandinos X., 1974-; Pallis, Evangelos, 1971- (IET telecommunications series, 2017)
The following topics are dealt with: 5G green mobile networks; fog computing; self-interference cancellation technique; mobile cloud computing; software-defined networking; Internet of Things; cognitive radio networks.